The influence of variable electrical conductivity on non-Darcian Casson nanofluid flow with first and second-order slip conditions - Obalalu, Adebowale Martins; Ajala, Olusegun Adebayo; Abdulraheem, Abdulrazaq; Akindele, Akintayo Oladimeji (Partial differential equations in applied mathematics : a spin-off of Applied Mathematics Letters, 2021)
Simulation of non-Darcian Casson flow subject to a second-order velocity slip and heat transfer due to nanofluid over a permeable stretching surface is exemplified numerically. The second-order velocity slip interaction is quite different from the first-order velocity slip as it results in two slip parameters that can effectively regulate the boundary layer development. To the best of the authors’ knowledge, this parameter was here incorporated for the first time in such a field of radiative Casson nanofluid flow. The model, which is governed by the system of PDEs, accomplishes the Chebyshev collocation Method (CCM). It is vital to remark that the account for the second-order slip velocity in the boundary conditions decreases the velocity component. In addition, the role of (Prandtl-number = 7 water) on the Skin friction coefficient becomes more significant when the Variable viscosity increases compared to the (Prandtl-number = 0.71 air). Also, non-Newtonian Casson fluid parameter show a solid characteristic when yield stress is more than the shear stress. Consequently, those parameters contribute to the cooling plate, while others have the opposite effect. Therefore, the cooling/heating mechanism can be developed with appropriate Casson fluid model and the control parameter. At last, this article includes some future recommendations.